Fully Automated Region Growing Segmentation of Brain Lesion in Diffusion-weighted MRI - Mohd Saad, Norhashimah; Abdullah, Abdul Rahim (IAENG, 2012)
Diffusion-weighted MRI, brain lesion,segmentation, split and merge, adaptive region growing.